Study on Gastrointestinal Evaluation of Iron Deficiency Anaemia Patients Attending at BIRDEM Hospital - Jamal, Mohammad Shah; Rahman, Md Anisur; Bhuiyan, Tareq M; Azam, MG; Mahbub, Shawhely; Rahman, Mahbubur; Mamoon, Abdullah Al (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Background: Anaemia is common among general population in developing Asian countries. Iron deficiency anaemia (IDA) is the commonest type of anaemia. It is usually due to chronic gastrointestinal blood loss. The standard of care for these patients with IDA includes evaluation of the Gastrointestinal (GI) tract for bleeding lesions. Iron deficiency anemia is considered as an alarm sign for the presence of possible GI malignancies, and inadequate evaluation of patients with IDA may delay the diagnosis of GI tumors especially colorectal cancer. Objective: To identify the gastrointestinal lesions endoscopically in patients with iron deficiency anaemia. To determine the usefulness of endoscopic procedures (both upper and lower GI) in diagnosis of underlying cause of iron deficiency. Method: This cross-sectional study was conducted to evaluate Iron deficiency anaemia in patients with or without GI symptoms during the period of July 2010 to December 2010 in the department of Gastroenterology, BIRDEM General Hospital. Sixty eight adult eligible patients with iron deficiency anaemia were taken as per inclusion criteria. All study subjects were underwent endoscopy and colonoscopic procedure after adequate preparation along with examination of their stool. Data were collected through faceto- face interview, observation and document review. Data were recorded and analyzed. Results: Majority of patients were 55 to 64 years age group (33.8%). Mean age ± SD of this study subject was 54.00 ±11.792 with maximum and minimum age 86 and 27 years respectively. More than half of the patients were female (51.5%) and rests were male 33 (48.5%). Among the study subjects, 70.58% patients had GI symptoms, 29.42% had non-GI symptoms. On stool examination, 17.64% patients had ova/cyst of helminthes; 82.36% were normal. Stool OBT revealed 11.8% positive and 88.2% negative. On upper GI endoscopy 32.4% had normal findings, 67.6% had some lesions. Majority of these lesions were ulcers and erosions (30.9%), malignancy (ca stomach) was 4.41%; others (which includes congestive gastropathy, reflux oesophagitis, vascular ectasias and helminthiasis) were 32.4%. On colonoscopy, 30.88% patients had normal colon; 69.12% had lesions. Among the lesions, most common lesion was hemorrhoids (36.76%); ca colon was 5.88% and others (includes ulcers, polyps, vascular ectasias and helminthes) were 26.47%. Patients with normal upper GI endoscopy- 50% had GI symptoms and 50% had non-GI symptoms whereas patients having lesions on upper GI endoscopy 80.4% had GI symptoms and 19.6% had non-GI symptoms. This difference was statistically significant (p<0.05). Patients with normal colonoscopy- 42.9% had GI symptoms and 57.1% had non-GI symptoms. On the other hand, patients having lesions on colonoscopy 70.6% had GI symptoms and 29.4% had non-GI symptoms. This was also statistically significant. Conclusion: Majority of the study population had lesions on endoscopy (both upper GI endoscopy and colonoscopy) including malignant lesions. Study showed that lesions are more common in patients with GI symptoms than those without GI symptoms (non-GI symptoms). Therefore, Routine endoscopic (both upper and lower GI) procedures is valuable in evaluating patients with iron deficiency anaemia- for diagnostic as well as therapeutic purposes. Effective treatment of patients with IDA is predicated on the identification of a specific lesion. J Bangladesh Coll Phys Surg 2015; 33(3): 126-132